The novel estrogen receptor beta agonist EGX358 and APOE genotype influence memory, vasomotor, and anxiety outcomes in an Alzheimer’s mouse model - Schwabe, M. R.; Fleischer, A. W.; Kuehn, R. K.; Chaudhury, S.; York, J. M.; Sem, D. S.; Donaldson, W. A.; LaDu, M. J.; Frick, K. M. (Frontiers in Aging Neuroscience, 2024)
IntroductionAlzheimer’s disease (AD) prevalence and severity are associated with increased age, female sex, and apolipoprotein E4 (APOE4) genotype. Although estrogen therapy (ET) effectively reduces symptoms of menopause including hot flashes and anxiety, and can reduce dementia risk, it is associated with increased risks of breast and uterine cancer due to estrogen receptor alpha (ERα)-mediated increases in cancer cell proliferation. Because ERβ activation reduces this cell proliferation, selective targeting of ERβ may provide a safer method of improving memory and reducing hot flashes in menopausal women, including those with AD. APOE genotype influences the response to ET, although it is unknown whether effects of ERβ activation vary by genotype.MethodsHere, we tested the ability of long-term oral treatment with a novel highly selective ERβ agonist, EGX358, to enhance object recognition and spatial recognition memory, reduce drug-induced hot flashes, and influence anxiety-like behaviors in female mice expressing 5 familial AD mutations (5xFAD-Tg) and human APOE3 (E3FAD) or APOE3 and APOE4 (E3/4FAD). Mice were ovariectomized at 5 months of age and were then treated orally with vehicle (DMSO) or EGX358 (10 mg/kg/day) via hydrogel for 8 weeks. Spatial and object recognition memory were tested in object placement (OP) and object recognition (OR) tasks, respectively, and anxiety-like behaviors were tested in the open field (OF) and elevated plus maze (EPM). Hot flash-like symptoms (change in tail skin temperature) were measured following injection of the neurokinin receptor agonist senktide (0.5 mg/kg).ResultsEGX358 enhanced object recognition memory in E3FAD and E3/4FAD mice but did not affect spatial recognition memory. EGX358 also reduced senktide-induced tail temperature elevations in E3FAD, but not E3/4FAD, females. EGX358 did not influence anxiety-like behaviors or body weight.DiscussionThese data indicate that highly selective ERβ agonism can facilitate object recognition memory in both APOE3 homozygotes and APOE3/4 heterozygotes, but only reduce the magnitude of a drug-induced hot flash in APOE3 homozygotes, suggesting that APOE4 genotype may blunt the beneficial effects of ET on hot flashes. Collectively, these data suggest a potentially beneficial effect of selective ERβ agonism for memory and hot flashes in females with AD-like pathology, but that APOE genotype plays an important role in responsiveness.